Representasi the Other dalam Novel Cinta Putih di Bumi Papua Karya Dzikry El Han: Tinjauan Sastra Perjalanan Carl Thompson - Kasimbara, Devi Cintia; Wahyuningsih (Kajian Linguistik dan Sastra, 2024)
Travel literature is a work that writes about the author's experience when traveling to a new andunfamiliar place. This research aims to raise and explore the form of representation of The Otherdescribed by Dzikry el Han in the novel Cinta Putih di Bumi Papua. The research method used in thisstudy is qualitative. By using Carl Thompson's travel writing theory, this paper will reveal the author'sculture and Papuan culture told in the novel. The results show that in the novel Cinta Putih di BumiPapua, there are various colonial discourses that are demeaning and othering the Papua people.Although the travel literature written by Dzikry is based on accurate data, it should be noted that thefact that a society consists of various individuals who have various characters so that it can be concludedthat travel literature will not be able to cover a society in a culture perfectly because the society consistsof various individuals who have their own life stories so that it would not be fair to judge a culturewithout seeing it as a whole.